Long-Term Skid Resistance Evaluation of GAC-16 Based on Accelerated Pavement Testing - Xinquan Xu; Yunhong Yu; Jun Yang; Chuanhai Wu (Advances in Materials Science and Engineering)
In this paper, four antiskidding surface test sections were paved to investigate the long-term skid resistance of the improved dense-graded asphalt concrete in Guangdong Province (GAC) using diabase fine aggregate instead of limestone. Four test sections were tested by the accelerated loading equipment (MLS11, mobile load simulator). The reduction law of the long-term skid resistance of GAC-16 was analyzed based on the accelerated pavement testing results. Prediction models of the GAC-16 skid resistance were also established and verified. The evaluation indexes of the long-term skid resistance of the asphalt pavement were introduced, and the antiskidding durability of different sections was evaluated. Results show that the initial British pendulum number (BPN) and mean texture depth (MTD) of the asphalt pavement cannot completely characterize its long-term skid resistance. With increasing loading cycles, the attenuation law of the BPN and MTD of GAC-16 denotes a fast reduction during the early stage, which gradually stabilizes. The relation between the skid resistance index and accelerated loading cycles was analyzed by nonlinear fitting according to the least-squares-method principle. The attenuation law of the BPN and MTD of GAC-16 with loading cycles was in accordance with the exponential and logarithmic models, respectively. The long-term antiskidding performance of the asphalt pavement could be accurately characterized using a stable BPN, loading cycles while reaching a stable BPN, the initial MTD value, and the MTD reduction rate as the evaluation indexes of the skid resistance of asphalt pavement. Compared with limestone fine aggregate, diabase fine aggregate can improve the long-term skid resistance of the asphalt mixtures.